Efisiensi produksi sawi pakcoy (Brasica rapa L.) di Desa Sumberejo Kota Batu - Dangkung, Lukas Irwantus; Pudjiastuti, Agnes Quartina; Khoirunnisa, Ninin (Journal of Agricultural Socio-Economics (JASE), 2020)
Pakcoy mustard (Brasica rapa L.) has a relatively high economic value in terms of low farming costs, so it has the potential to continue to be developed because the community widely consumes it both in fresh and processed form. The development of the population and industrial users of pakcoy mustard as a raw material causes this commodity's demand to continue to increase. This study aimed to analyze the production efficiency of pakcoy mustardÂ  in the village of Sumberejo. This village is one of the pakcoy mustard production centers in Batu City. The data was collected through interviews with 45 pakcoy farmers selected from 350 pakcoy farmers in the research location. The data that has been collected were analyzed with the Cobb-Douglas production function, then the allocative efficiency was calculated. The results showed that the use of seeds, TSP, and NPK fertilizers in pakcoy mustard production in the village of Sumberejo, Batu City was not allocatively efficient.